Kristologi dalam Tradisi Reformasi : Pemahaman tentang Yesus Kristus dalam Perspektif Reformatoris - Jesica Carolina; Septania Adut; Helena Regalia Ujabi; Sarmauli Sarmauli (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
The Protestant Reformation had a significant impact on the development of Christian theology, especially in the field of Christology. This study aims to examine the thoughts of Martin Luther and John Calvin regarding the role of Christ in the process of human salvation. The method used is a qualitative approach with a literature study technique, which examines the theological works of the two Reformers. The results of the study show that Luther emphasized the personal relationship between humans and Christ as savings, as well as the real presence of Christ in the sacrament as a form of God's grace that can be experienced personally. Meanwhile, Calvin developed the concept of three placements of Christ as prophet, priest, and king which emphasized the overall role of Christ in salvation, and viewed the sacrament as a spiritual means to strengthen the faith of believers. Through this study, it can be concluded that Christology in the Reformation tradition provides a strong, systematic, and relevant theological basis for the development of contemporary Protestant teachings, both in doctrinal aspects and the practice of life of faith.